2002
DOI: 10.1051/0004-6361:20021421
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared coronagraph images of IRC +10216

Abstract: Abstract. We present J, H and K band coronagraph images of the circumstellar envelope around IRC +10216 (CW Leo) obtained with a near infrared camera, CIAO and the 8.2 m Subaru telescope. A circular occulting mask of 2 in diameter was used to block out the light from the bright central object. The images show 2 collimated radial structures to the NNW and WNW, 2 fan-like structures to the S and NE, respectively, and 3 arc-like structures at a radius of 4 to 5 arcsec from the stellar center. We compare this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
5
4
0
Order By: Relevance
“…Both of our models show that the axisymmetric structure is caused by equatorial mass loss and is not a bi-polar outflow as previously described (e.g. Murakawa et al 2002).…”
Section: Previous Observationssupporting
confidence: 85%
See 1 more Smart Citation
“…Both of our models show that the axisymmetric structure is caused by equatorial mass loss and is not a bi-polar outflow as previously described (e.g. Murakawa et al 2002).…”
Section: Previous Observationssupporting
confidence: 85%
“…IRC+10216 has been observed from very large (100s of arcseconds) to very small (milli-acrseconds) spatial scales, mostly at infrared wavelengths. Many of these studies have found evidence for axi-symmetric structure Mauron & Huggins (2000); Skinner et al (1998); Murakawa et al (2002); Leão et al (2006) and have only indirectly inferred the possible existence of an equatorial density enhancement of gas and dust in the inner regions of the wind. However, so far with direct imaging, conclusive evidence for such a density enhancement has been elusive because observations were either done at infrared wavelengths, using regular intensity imaging, or with coronographs that obscure the inner regions of the circumstellar shell.…”
Section: Previous Observationsmentioning
confidence: 99%
“…2 radius from the NE to the W. These features are also seen in previous images with middle-size FOVs (e.g. Kastner & Weintraub 1994;Skinner et al 1998;Murakawa et al 2002). The NE and S lobes have polarizations of 15−20%, and the NW lobe has 15−24%.…”
Section: Polarimetric Imagesupporting
confidence: 73%
“…The wavelengths in figures 7a and 7b are J and H , respectively, but such a difference does not change this discussion. This kind of advantage is also seen in results of the circumstellar envelope around IRC + 10 216 [Murakawa et al (2002) for coronagraphic images and Murakawa et al are in prepreparation of a paper for a non-coronagraphic image].…”
Section: Coronagraph Imaging Of a Red Supergiant Vy Cmamentioning
confidence: 70%